765 kV Transmission Line Design (Electrical Section) - Aydin Sakhavati; Mostafa Yaltagiani; Shirin Saleh Ahari; Seyed Mahdi Mahaei (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Nowadays, due to the ever increasing energy consumption and power supply optimization, it is required to construct new power plants, substations and transmission lines. In Iran, also, because of increasing demand for electrical energy, for a significant power loss reduction in power transmission over long distances, and to construct high transmission lines that lead to reduction in the economic costs of transmission lines, the transmission lines must be considered at extra high voltage (EHV) levels. These EHV levels should be compared with the low voltage levels in order to extract the benefits. Therefore, in this paper, a review has been conducted on the types of 765 kV transmission lines used in different countries and a comparison between them and the low voltage levels have been performed. Accordingly, the advantages of EHV transmission lines are summarized. Finally, designing a line of 765 kV single-circuit with 6 conductors per bundle based on existing standards is presented.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1591